Microwave shielding characteristics of thermoplastic/graphene composites with montmorillonite (bentonite) clay addition for improved thermal stability. Issue 3 (11th February 2022) - Joseph, Jomy; Koroth Koyadan, Ajith; Sidpara, Ajay M.; Paul, Jinu
ABSTRACT: PMMA/graphene/Bentonite and PVC/graphene/Bentonite hybrid composites were prepared by solution casting method. Thermal stability, electrical conductivity and EMI shielding effectiveness in X-band were studied in detail. PVC composite with 5 wt.% Bentonite exhibited an enormous improvement in the thermal stability compared to the PVC/graphene counterpart. However, increase in Bentonite content in the hybrid composites reduced their electrical conductivity and resulted in lower overall shielding effectiveness in X band. The hybrid nanocomposites were found to have a significantly stronger influence of absorption in the overall shielding effectiveness when compared with respective polymer/graphene composites. The detailed microstructural/mechanical characterization elucidates the underlying mechanisms.